2012
DOI: 10.1371/journal.pone.0030075
|View full text |Cite|
|
Sign up to set email alerts
|

BMP-9 Induced Endothelial Cell Tubule Formation and Inhibition of Migration Involves Smad1 Driven Endothelin-1 Production

Abstract: BackgroundBone morphogenetic proteins (BMPs) and their receptors, such as bone morphogenetic protein receptor (BMPR) II, have been implicated in a wide variety of disorders including pulmonary arterial hypertension (PAH). Similarly, endothelin-1 (ET-1), a mitogen and vasoconstrictor, is upregulated in PAH and endothelin receptor antagonists are used in its treatment. We sought to determine whether there is crosstalk between BMP signalling and the ET-1 axis in human pulmonary artery endothelial cells (HPAECs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 57 publications
4
40
2
Order By: Relevance
“…However, changes in expression of cxcr4a and edn1 cannot fully explain defects in vessel architecture resulting from loss of alk1. Although ALK1 signaling can repress CXCR4 or induce EEN1 in cultured endothelial cells (Star et al, 2010;Park et al, 2012;Young et al, 2012), supporting our in vivo data, previous work has demonstrated that increased cxcr4a is not necessary nor is loss of edn1 sufficient for AVM development , and additional work has demonstrated that concomitant increase in cxcr4a and loss of edn1 is insufficient to generate AVMs (E. Rochon and B.L.R., unpublished). Thus, further work is required to define the molecular mechanisms and cellular behaviors that lead to arterial enlargement in the absence of alk1.…”
Section: Discussionsupporting
confidence: 87%
“…However, changes in expression of cxcr4a and edn1 cannot fully explain defects in vessel architecture resulting from loss of alk1. Although ALK1 signaling can repress CXCR4 or induce EEN1 in cultured endothelial cells (Star et al, 2010;Park et al, 2012;Young et al, 2012), supporting our in vivo data, previous work has demonstrated that increased cxcr4a is not necessary nor is loss of edn1 sufficient for AVM development , and additional work has demonstrated that concomitant increase in cxcr4a and loss of edn1 is insufficient to generate AVMs (E. Rochon and B.L.R., unpublished). Thus, further work is required to define the molecular mechanisms and cellular behaviors that lead to arterial enlargement in the absence of alk1.…”
Section: Discussionsupporting
confidence: 87%
“…Endochondral bone formation occurs in close spatial and temporal association and proximity to capillary invasion, so that angiogenesis and osteogenesis must be tightly coupled (Olsen et al, 2000;Wan et al, 2010;Wang et al, 2007). Conflicting results have implicated BMP9 as either an angiogenesis inducer in endothelial cells (Castonguay et al, 2011;Cunha et al, 2010;Mitchell et al, 2010;Park et al, 2012;Scharpfenecker et al, 2007;Suzuki et al, 2010;Yao et al, 2012) or as a potent anti-angiogenic factor (David et al, 2008). Although it is well recognized that osteogenic and angiogenic pathways are well coordinated during bone formation (Wan et al, 2010), it is unclear how these processes are linked in MSCs stimulated by osteogenic factors, such as BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Cell lysates were prepared as described previously [27] and were precipitated using cold acetone, and air-dried. The resulting pellets were dissolved in 50ul 1XSDS sample buffer and cleared by centrifugation.…”
Section: Western Blotmentioning
confidence: 99%